2016
DOI: 10.4103/2045-9912.184720
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy for traumatic brain injury: bench-to-bedside

Abstract: Traumatic brain injury (TBI) is a serious public health problem in the United States. Survivors of TBI are often left with significant cognitive, behavioral, and communicative disabilities. So far there is no effective treatment/intervention in the daily clinical practice for TBI patients. The protective effects of hyperbaric oxygen therapy (HBOT) have been proved in stroke; however, its efficiency in TBI remains controversial. In this review, we will summarize the results of HBOT in experimental and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…As a nondrug and noninvasive treatment, hyperbaric oxygen (HBO) therapy has been used as a treatment for TBI since 1960s 4. However, the efficiency of HBO therapy remains extremely controversial 57. Several studies have reported that HBO therapy improved the neurological deficits and cognitive impairments of patients in the acute phase of severe TBI 8,9.…”
Section: Introductionmentioning
confidence: 99%
“…As a nondrug and noninvasive treatment, hyperbaric oxygen (HBO) therapy has been used as a treatment for TBI since 1960s 4. However, the efficiency of HBO therapy remains extremely controversial 57. Several studies have reported that HBO therapy improved the neurological deficits and cognitive impairments of patients in the acute phase of severe TBI 8,9.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperbaric oxygen therapy used for the management of TBI and it reported to posses neuroprotective effect by acting on inflammatory pathway [ 11 ]. There is several limitations of this therapy that precise the use of HO in TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Complications from TBI can occur even years after the injury, such as post-concussion syndrome, in which severe headaches and other symptoms appear [11]. Hypoxia and TBI are strongly tied when cerebral blood vessels are damaged, hence HBOT has been extensively studied as a potential treatment for TBI [134][135][136].…”
Section: Tbimentioning
confidence: 99%